Immunogenicity and safety of an AS03-adjuvanted H7N1 vaccine in adults 65 years of age and older: A phase II, observer-blind, randomized, controlled trial. Issue 15 (4th April 2017) - Madan, Anuradha; Ferguson, Murdo; Rheault, Paul; Seiden, David; Toma, Azhar; Friel, Damien; Soni, Jyoti; Li, Ping; Innis, Bruce L.; Schuind, Anne
Highlights: AS03-adjuvanted H7N1 vaccine formulations were evaluated in adults ≥65 years of age. Post-dose 2, 69.6%–88.7% of participants per group had HI antibody titers ≥1:40. Cross-reactivity to a vaccine-heterologous H7N9 strain was observed. All H7N1 vaccine formulations had a clinically acceptable safety profile. Abstract: Background: H7 influenza strains can cause severe and often fatal human infections, especially in the elderly. This phase II, observer-blind, randomized trial (www.ClinicalTrials.gov :NCT01949090 ) assessed the immunogenicity and safety of a novel AS03-adjuvanted H7N1 vaccine that may serve as a model H7-subtype vaccine. Methods: 360 adults ≥65 years of age in stable health received either 1 of 4 adjuvanted A/mallard/Netherlands/12/2000 split virion vaccine formulations (3.75 μg or 7.5 μg hemagglutinin adjuvanted with either AS03A or AS03B ) or saline placebo, given as a 2-dose series. Immunogenicity was assessed using hemagglutination-inhibition (HI) and microneutralization (MN) assays for the per-protocol cohort, comprising 332 participants at 21 days post-each dose, 332 at month 6, and 309 at month 12 (HI assay only). Safety was assessed up to month 12 for all participants who had received ≥1 dose (360 participants). Results: For H7N1 HI antibody assessment at day 42 (21 days post-dose 2), seroprotection rates (SPR) in the vaccinated groups were 69.6%–88.7%, seroconversion rates (SCR) 69.6%–88.5%, mean geometric increase (MGI) 11.0–18.9, and HI geometric mean titers (GMTs) 55.0–104.8. These parameters declined by month 6 and month 12. Microneutralization GMTs were 46.2–74.7 in the vaccinated groups at day 42, while vaccine response rate (VRR; proportion with ≥4-fold increase in MN titer) was 46.4%–81.5%. For the cross-reactive H7N9 strain, at day 42, HI GMT were 64.3–201.3, SPR 78.6%–96.3%, SCR 79.3%–96.3%, and MGI 14.1–37.7; MN GMTs were 44.0–85.6, and VRR 46.4–85.2%. The most frequent solicited symptom was injection site pain (41.7%–65.0% of vaccine recipients). In total, 40 participants reported 67 serious adverse events; none were considered causally related to vaccination. Conclusions: In adults aged ≥65 years, the adjuvanted H7N1 vaccine was immunogenic after 2 doses, and had an acceptable safety profile. www.ClinicalTrials.gov :NCT01949090 .